89Factors associated with pneumococcal nasopharyngeal carriage: a systematic review. (2nd September 2021) - Neal, Eleanor; Chan, Jocelyn; Russell, Fiona M.; Nguyen, Cattram. D
Abstract: Background: Pneumococcal disease is a major contributor to global childhood morbidity and mortality. Pneumococcal carriage is a prerequisite for pneumococcal disease. Identifying factors associated with pneumococcal carriage can aid public health intervention programs. It is unknown if risk factors for pneumococcal carriage differ between low, middle, and high-income countries. We present preliminary findings of our systematic review of factors associated with pneumococcal carriage in community settings, in all ages. Methods: A systematic search for pneumococcal nasopharyngeal carriage studies, published in English before July 2019. Two researchers independently reviewed studies that described factors associated with pneumococcal nasopharyngeal carriage. Study quality was assessed using the NIH Study Quality Assessment Tools. Results are presented as narrative summaries due to heterogeneity amongst factor definitions. Results: Preliminary results are shown. Sixty-seven studies were included. 49% were conducted in high-income countries. Pneumococcal prevalence ranged from 0.3%-97%, 2.6%-89.6%, 14%-73%, 1.6%-82.4% in low-, lower-middle, upper-middle, and high-income classifications. Age, respiratory tract infection symptoms, living with young children, poverty, exposure to smoke, and season were positively associated with pneumococcal carriage in all income classifications. Conclusions: Pneumococcal carriage prevalence was highest in low-income classifications. Pneumococcal carriage is associated with similar factors across income classifications. Differences in prevalence of risk factors associated with pneumococcal carriage by income classification may contribute to differences in carriage prevalence by income classifications. Key messages: Pneumococcal carriage is considered a prerequisite for pneumococcal disease. Pneumococcal carriage prevalence is highest in low-income countries, however preliminary results suggest risk factors for carriage may be similar across income classifications.